Human Amniotic Epithelial Cells Promote the Proliferation of Human Corneal Endothelial Cells by Regulating Telomerase Activity via the Wnt/β-catenin Pathway. (1st February 2021) - Liu, Jiayan; Wen, Ye; Luo, Wei; Liu, Yingying; Sha, Xiangyin
ABSTRACT: Purpose: Human amniotic epithelial cells (HAECs) have regenerative properties and low immunogenicity, which have enabled their use without immune rejection in regenerative medicine applications, such as wound repair, corneal surgery and burn repair. The aim of this study was to explore the potential role of HAECs in the proliferation of human corneal endothelial cells (HCEnCs) and the possible mechanism of regulation. Methods: HAECs and HCEnCs were isolated from donated tissue samples and were cultured; the collected HAEC culture medium (HAEC-Me) was added to the human corneal endothelium medium (CEM) to establish the HAEC-CM system. HCEnCs were cultured in CEM, 20%HAEC-Me, 20% HAEC-CM, 20% HAEC-CM supplemented with a GSK-3β inhibitor TWS119 or CEM supplemented with TWS119. Then, cell proliferation, apoptosis, cell cycle progression, telomerase activity, and Wnt/β-catenin pathway-related protein levels were assessed. Results: We found that the HCEnCs cultured in the 20% HAEC-CM had increased proliferative capacity, telomerase activity and β-catenin and Tcf4 expression levels, and they had a decrease in the rate of apoptosis and α-SMA expression when they were compared with the HCEnCs cultured in the 20% HAEC-Me. After GSK-3β was inhibited by TWS119, HCEnCs cultured in CEM or 20% HAEC-CM had an increased proliferative capacity, telomerase activity, β-catenin/Tcf4 expression and a decreased α-SMA expression, and they had a decreased apoptotic rate. Conclusions: These data indicate that the human amniotic epithelial cells microenvironment can promote the proliferation of human corneal endothelial cells, which may be related to regulating telomerase activity and epithelial-to-mesenchymal transition (EMT) via the Wnt/β-catenin pathway.